A Suspended Individual: The Close-up as Deterritorialisation and Political Device of Control - Matti, Felipe Andres (2025)
This paper examines the interplay between affectivity, individuality and territory through the lens of Gilles Deleuze’s philosophy of the image. To such end, this article employs a philosophical and conceptual analysis grounded in Gilles Deleuze’s cinema theory. The method is qualitative and interpretive, focusing on conceptual elaboration, theoretical synthesis and philosophical critique, rather than empirical research. The article finds that the close-up suspends individuation and expresses the pure affect by deterritorialising the subject. However, in contemporary media, this potential is reterritorialised through political messaging that uses close-up imagery to fix affect within ideological frameworks. Instead of expressing affect, political figures represent and capture it, neutralising its disruptive force.